Gaia Data Release 2: kinematics of globular clusters and dwarf galaxies around the Milky Way (Corrigendum) - Helmi, Amina; Bastian, Ulrich; Biermann, Michael; Bailer-Jones, Coryn A. L.; Gracia-Abril, Gonzalo; Altmann, Martin; Jordan, Stefan; Löffler, Wolfgang; Sagristà Sellés, Antoni (Astronomy and astrophysics, 2020)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics
This article is an erratum for "Gaia Data Release 2" (Vol. 616(2018) Artikel-Nummer A12, 47 Seiten)
Gesehen am 28.09.2020